Impact of heritage tourism on local community in Sabah, Malaysia - Aljohani Nadiyah Mazi; Er Ah Choy (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sabah, a Malaysian state, has become a popular destination which attracts visitors who are interested in art, architecture handicrafts, traditional attire, music and dance. However, due to new developments coupled with the lack of information and knowledge concerning the historical and architectural significance, precious cultural heritage sites are under threat. This study aims to determine the effect of heritage tourism on the local community in Sabah because this state is currently undergoing the phase of tourism development and heritage tourism. This study also examines the factors affecting heritage tourism in Sabah. It adopts the quantitative approach for collecting and analyzing the data. The sample of the study is comprised of 130 individuals living in Sabah who are selected through stratified random sampling technique. The obtained data are processed using SPSS software. The findings indicate a positive significant impact of heritage tourism on Sabah local community. The results of the study also reveal that economic and cultural aspects significantly affect heritage tourism. The results of the study also show that the heritage tourism in Sabah and the local community encounter challenges in promoting heritage tourism, namely, the maintenance and improvement of infrastructure. Therefore, this study recommends that the archaeological sites should be restored in the city so as to strengthen and prepare heritage and make it more attractive to the local and international tourists. Furthermore, the infrastructure of the city should be developed in order to be able to receive more tourists. The study also proposes that festivals and activities should be organized in the sites of Sabah as they contribute to boosting the number of visitors. This pioneering study on heritage tourism in Sabah provides implications which could be useful for decision makers in Sabah as well as interested researchers.